HDAC1 promoted migration and invasion binding with TCF12 by promoting EMT progress in gallbladder cancer - He, Junyi (Oncotarget, 2016)
The identification of prognostic markers for gallbladder cancer is needed for clinical practice. Histone deacetylases (HDACs) play an important role in tumor development and progression by modifying histone and non-histone proteins. However, the expression of HDAC1 in patients with gallbladder cancer is still unknown. Here, we reported that HDAC1 expression was elevated in cancerous tissue and correlated with lymph node metastasis and poorer overall survival in patients with GBC. Knockdown of HDAC1 using lentivirus delivery of HDAC1-specific shRNA abrogated the migration and invasion of GBC cells in vitro. TCF-12, as the HDAC1 binding protein, has also correlates with poor prognosis in GBC patients. And there is a positive correlation between HDAC1 and TCF-12 which leading the high invasion and migration ability of GBC cells. Taken together, our data suggested that HDAC1 and TCF-12 are a potential prognostic maker and may be a molecular target for inhibiting invasion and metastasis in GBC.